Analyzing the effect of aromatic therapy on human energy level using resonant field imaging (RFI) / Nurul Baizura Zainal - Zainal, Nurul Baizura
This technical paper investigates the effectiveness of aromatic therapy on human energy level using resonant field imaging system (RFI). The results show the health level of female students using physiological analysis. Frequency measurement of human radiation is taken for 21 female students of Electrical Engineering before and after using aromatherapy during their menstruation period. The objective is to study the effectiveness of lavender in order to reduce the pain and discomfort during menstruation. Based on the results presented, it is concluded that lavender is effective in increasing human health condition, particularly for women during menstruation period. It also implies that pure and high frequency electrofield energy is projected from parts of the body.